Modelling polarized X-ray pulses from accreting millisecond pulsars with X-PSI, using different hot spot locations and shapes - Salmi, Tuomo; Dorsman, Bas; Watts, Anna L.; Bobrikova, Anna; Di Marco, Alessandro; Loktev, Vladislav; Papitto, Alessandro; Pilia, Maura; Poutanen, Juri; Rankin, John (OXFORD UNIV PRESS, 2025)
We present an analysis of polarized X-ray pulses based on simulated data for accreting millisecond pulsars (AMPs). We used the open-source X-ray Pulse Simulation and Inference code (previously applied to NICER observations), which we upgraded to allow polarization analysis. We provide estimates of how well neutron star (NS) parameters can be constrained for the Imaging X-ray Polarimetry Explorer (IXPE) and find that strong limits on the hot region geometries can be hard to obtain if the emitting hot region is large and the number of polarized photons relatively small. However, if the star is bright enough and the hot regions are small and located so that polarization degree is higher, the observer inclination and hot spot colatitude can be constrained to a precision of within a few degrees. We also found that the shape of the hot region, whether a circle or a ring, cannot be distinguished in our most optimistic scenario. Nevertheless, future X-ray polarization missions are expected to improve the constraints, and already the recent AMP polarization detections by IXPE should help to infer the NS mass and radius when combined with modelling of X-ray pulse data sets that do not contain polarization information.